2006
DOI: 10.1097/01.pas.0000209855.28282.ce
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-1 (PD-1) is a Marker of Germinal Center-associated T Cells and Angioimmunoblastic T-Cell Lymphoma

Abstract: Programmed death-1 (PD-1), a member of the CD28 costimulatory receptor family, is expressed by germinal center-associated T cells in reactive lymphoid tissue. In a study of a wide range of lymphoproliferative disorders, neoplastic T cells in 23 cases of angioimmunoblastic lymphoma were immunoreactive for PD-1, but other subtypes of T cell and B cell non-Hodgkin lymphoma, as well as classic Hodgkin lymphoma, did not express PD-1. The pattern of PD-1 immunostaining of neoplastic cells in angioimmunoblastic lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
234
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(262 citation statements)
references
References 20 publications
22
234
2
4
Order By: Relevance
“…Recent studies have suggested that T FH cells and neoplastic AITL cells share the expression of many phenotypic markers, and that the AITL cells may be derived from T FH cells. [64][65][66][67][68] Examples of these markers expressed by both T FH cells and neoplastic AITL cells include Bcl6, CXCR5, PD-1, CD40L, OX40 and CXCL13. However, neoplastic AITL cells, in contrast to T FH cells, express CD10, which is a cell surface zinc metalloendopeptidase expressed in a variety of normal and neoplastic tissues.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
“…Recent studies have suggested that T FH cells and neoplastic AITL cells share the expression of many phenotypic markers, and that the AITL cells may be derived from T FH cells. [64][65][66][67][68] Examples of these markers expressed by both T FH cells and neoplastic AITL cells include Bcl6, CXCR5, PD-1, CD40L, OX40 and CXCL13. However, neoplastic AITL cells, in contrast to T FH cells, express CD10, which is a cell surface zinc metalloendopeptidase expressed in a variety of normal and neoplastic tissues.…”
Section: The Darker Side Of Follicular Helper T Cells S Shekhar and Xmentioning
confidence: 99%
“…5) [9,[21][22][23][24]. Typically, the tumor cells of AITL have a T-helper cell phenotype expressing CD3, CD4, and frequently CD10, similar to a subset of normal GC-Th cells [23,25] (Table III).…”
Section: Angioimmunoblastic T-cell Lymphomamentioning
confidence: 99%
“…PD-1 is expressed on activated T cells, particularly on Tfh cells. PD-1 promotes cognate T-B interactions and provides an inhibitory signal to Tfh cells [37]. Zhu et al [38] showed that the percentages of CD3 …”
Section: Cxcr5mentioning
confidence: 99%